Implementation of the Tri Hita Karana Concept in the Science Learning Process - Kadek Ayu Astiti; Made Sutajaya; Wayan Suja; Ida Bagus Made Astawa; Ni Made Ayu Suryaningsih; Christiani Endah Poerwati; I Komang Wisnu Budi Wijaya (Jurnal Penelitian Pendidikan IPA, 2024)
Tri hita karana are three sources of happiness in life. The three sources of happiness include 1) the relationship between humans and God (parahyangan), 2) the relationship between humans and other humans (pawongan), 3) the relationship between humans and the environment (palemahan). The aim of this research is to determine the implementation of the tri hita karana concept in the learning process. This research is library research, where the data obtained is secondary data obtained from trusted sources, both books and scientific articles. The literature used was obtained through searches from Google Scholar. The results of this research show that the implementation of the tri hita karana concept in science learning process is able to develop students' full potential, both intellectual, spiritual, social and emotional, as well as forming a generation that has noble character and cares about the environment.